2011
DOI: 10.1007/s00268-011-1198-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Non‐cirrhotic and Non‐malignant Portal Vein Thrombosis: A Systematic Review

Abstract: The natural history of acute PVT is poorly described. Spontaneous resolution of acute portal vein thrombosis is uncommon. Early anticoagulation results in a satisfactory rate of recanalization with minimal procedure-associated morbidity. Thrombolysis should be used with caution and only considered if the disease is progressive and signs of mesenteric ischemia are present. Further well-designed trials with precise outcome reporting are needed to improve our understanding of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 44 publications
2
93
0
4
Order By: Relevance
“…They also determined that at least six months of oral anticoagulation is effective in reducing long-term morbidity and mortality in cases of portal vein thrombosis occurring concurrently with SMV or SV. [20] Correspondingly, in cases with prothrombotic risk factors, long-term or life-long anticoagulant treatment could be considered, as stated in recent published consensus statements. [7,20,21] After diagnosis with MVT, anticoagulation should be started promptly with the administration of enoxaparin 100 mg/kg twice daily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also determined that at least six months of oral anticoagulation is effective in reducing long-term morbidity and mortality in cases of portal vein thrombosis occurring concurrently with SMV or SV. [20] Correspondingly, in cases with prothrombotic risk factors, long-term or life-long anticoagulant treatment could be considered, as stated in recent published consensus statements. [7,20,21] After diagnosis with MVT, anticoagulation should be started promptly with the administration of enoxaparin 100 mg/kg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Correspondingly, in cases with prothrombotic risk factors, long-term or life-long anticoagulant treatment could be considered, as stated in recent published consensus statements. [7,20,21] After diagnosis with MVT, anticoagulation should be started promptly with the administration of enoxaparin 100 mg/kg twice daily. The reported overall mortality rate of 50% in the literature is mainly attributed to difficulties in diagnosis and subsequent delay of necessary therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the management decisions have to be individualized depending on the local expertise, since there is lack of randomized controlled trials. A systematic review reported that upto 117 A recent multicenter 2 year follow up study evaluated 102 patients of acute PVT unrelated to cirrhosis and anticoagulation was given in 95 patients. 45 Following anticoagulation 1 year portal vein recanalization rate was 39% and no recanalization occurred beyond 6 months after initiation of anticoagulation.…”
Section: Anticoagulationmentioning
confidence: 99%
“…A 2011 systematic review showed that more than 80% of acute PVT cases do not resolve without the use of anticoagulation. 36 And for those that do recanalise without such drugs, it is either due to the spontaneous resolution of a self-limiting illness, such as acute pancreatitis, or due to the fact that the thrombosis load was very small. 36 In the systematic review, the time taken for recanalisation ranged from a few days to over 6 months indicating, in some cases, long-term anticoagulation may be needed for recanalisation.…”
Section: Anticoagulationmentioning
confidence: 99%